Writing with AI: What College Students Learned from Utilizing ChatGPT for a Writing Assignment - Changzhao Wang; Stephen J. Aguilar; Jennifer S. Bankard; Eric Bui; Benjamin Nye (MDPI AG, 2024)
To support the integration of AI in education, this empirical study investigated what lessons college students learned from using Generative AI for writing. We recruited 47 students in the United States from a university writing course. Students completed an assignment in which they used Generative AI tools (e.g., ChatGPT) to draft an application letter or personal statement. Data were collected using a survey of five open-ended questions about their writing process, what worked, what did not work, how to better write with AI, and general lessons learned. We applied thematic analysis and sentiment analysis methods to analyze students' responses. Results show that (1) students went through multiple rounds of prompting; (2) students identified strengths of AI, such as connection to topic, template generation, and sentence quality; (3) the weaknesses of AI included general language, robotic tone and lacking emotion, lacking personal voice, and lacking critical thinking; (4) students wished to improve AI-generated writing by adding personal stories, connections to posting, feelings and thoughts, and deleting repetitive language; and (5) their overall attitudes toward AI tool were positive. We believe our findings can help relieve some concerns about cheating with AI. We also suggested strategies to regulate the use of AI.